Komunikasi Publik Dalam Pengawasan Peraturan Walikota Lubuk Linggau Nomor 1 Tahun 2019 Tentang Pesta Malam - Benedictus Filius; Suratman (STAI Bumi Silampari, 2025)
This study examines the effectiveness of public communication in monitoring the implementation of the Mayor of Lubuk Linggau Regulation No. 1 of 2019 concerning Night Parties through an evaluation of public perceptions as the target group of the policy. The regulation aims to govern the organization of night parties in order to maintain public order, security, and community comfort. Employing a quantitative approach with a survey method involving 94 respondents, the study evaluates five dimensions of policy implementation based on Dunn’s (2003) framework: effectiveness, efficiency, adequacy, equity, and responsiveness. Data were collected using a structured questionnaire with a Likert scale and analyzed through descriptive statistics, comparative tests, and a composite index. The results indicate a Public Perception Index (PPI) score of 64.51, suggesting a fairly good perception of policy implementation. The adequacy dimension received the highest score (2.106), while efficiency had the lowest (1.611). An ANOVA test revealed significant differences among the dimensions (F = 14.397, p < 0.001). These findings suggest that while the public perceives the substance of the regulation as adequate, the efficiency of its implementation still requires improvement. The study recommends enhancing licensing mechanisms, strengthening coordination among stakeholders, improving policy socialization, and optimizing monitoring systems to increase the effectiveness of public communication and the overall implementation of the night party policy in Lubuk Linggau City.